Vanadium and Tannic Acid-Based Composite Conversion Coating for 6063 Aluminum Alloy - Zhu, Wen; Chen, Furui; Luo, Youbin; Su, Zhijun; Li, Wenfang; Yi, Aihua; Liao, Zhongmiao; Li, Kang; Chen, Ken; Hu, Yiwen; Xu, Yashu; Guo, Sinan (Frontiers in Materials, 2021)
In this study, a vanadium (V) and tannic acid-based composite conversion coating (VTACC) was prepared on 6063 aluminum alloy (AA6063) to increase its corrosion resistance. The surface morphology and compositions of the VTACCs were characterized using scanning electron microscopy (SEM), energy dispersive spectrometry (EDS), and X-ray photoelectron spectroscopy (XPS). The corrosion resistance of the coatings was investigated by linear polarization and electrochemical impedance spectra (EIS). The self-healing ability of the coating was detected by SEM, EDS, and scanning vibrating electrode technique (SVET) measurements. The coating mainly consisted of metal oxides, including Al2O3, VO2, V2O3, and V2O5 and metal organic complexes (Al and V-complexes). The electrochemical measurement results indicated that the best corrosion resistance of VTACC was acquired when the treatment time was 12 min. Furthermore, because a new coating with vanadium rich oxide was developed on the scratch area, artificial scratches VTACC surfaces were repaired after several days of immersion in 3.5-wt% NaCl solution.